2020
DOI: 10.1177/1055665620959989
|View full text |Cite
|
Sign up to set email alerts
|

Educational Attainment of Children Born with Unilateral Cleft Lip and Palate in the United Kingdom

Abstract: Objective: This study evaluated association between functional outcomes in children born with unilateral cleft lip and palate (UCLP) and educational attainment. Design: Cleft Care UK (CCUK) was a United Kingdom (UK) wide cross-sectional study. Setting: UK Cleft Teams (data collected from all UK sites providing centralized cleft services). Patients, Participants: Five-year olds born with nonsyndromic UCLP (n = 268). Main Outcome Measure(s): National tests for educational attainment Key Stage 1 (KS1) undertaken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…However, the sample size is limited, and more studies are needed to examine the effect of cleft laterality. The tendency in England and Sweden that grades of females with clefts were more negatively affected than grades of males with clefts 6 9 was not replicated.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…However, the sample size is limited, and more studies are needed to examine the effect of cleft laterality. The tendency in England and Sweden that grades of females with clefts were more negatively affected than grades of males with clefts 6 9 was not replicated.…”
Section: Discussionmentioning
confidence: 88%
“…Indirect effects such as school absence have been found to affect educational attainment of children born with cleft in England, 7 whereas results from Western Australia showed that absence from school did not differentially disadvantage these children. 32 Low self-confidence has also been found to affect educational attainment for cleft children, 6 and appearance, social acceptance and interactions, bullying and poor integration in the school system may also play a role. 24 33–36 Several of these factors could be modifiable and thus important to identify.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations